ANALISIS WARNA PADA INTERIOR INTERNET CAFE FUSION RISE - chalik, chris; Andrianto, Andrianto (Program Studi Desain Interior Unikom, 2022)
This research aims to analyze the application of color to the Internet café Fushion Rise, in Jatinangor, Sumedang regency. where the explosion of the online gaming industry in the world, especially multiplayer online games, has a significant impact on the proliferation of internet cafés in Indonesia, internet cafés that were initially only public facilities to get internet access, transformed into internet café, which in addition to offering higher internet speeds, better hardware specifications, and also obliged to provide comfort and a good gaming atmosphere. Therefore, internet café requires interior color design that can achieve the goal of a good gaming experience and comfort, so that internet café visitors can feel at home in playing in the internet café Fushion Rise. The gaming atmosphere can be formed from the perception aspect of gamers psychology and socio-cultural aspects of gamers. Both aspects can influence each other and create an atmosphere and experience of play. This research focuses on analyzing the application of color to the interior of icafe Fushion Rise according to the theme and concept of internet café interior design. This study will find the relationship of the colors contained in the elements that make up the space and the application of the color in the room. The research method used in this research is a quantitative research method with a descriptive analysis approach. Data collection techniques through surveys to internet café visitors and also discussions. The results of the data analysis, it was obtained that the application of color to the elements forming the interior space in the internet café can convey the atmosphere and affect the playing experience. Keywords: atmosphere, Cafe Fushion Rise, interior, internet cafe, color